Information and communication technologies in dental education: students’ perceptions - Alessandra Martins Ferreira Warmling; Cláudio José Amante; Ana Lúcia Schaefer Ferreira de Mello (Revista Sul-Brasileira de Odontologia, 2015)
Among teaching and learning methods, those using Information and Communication Technologies as new dental education possibilities are based on the student’s knowledge construction and the development of new capabilities such as innovation, creativity, autonomy and communication. Objective: To demonstrate the use of information and communication technologies (ICTs) as support tools for teaching-learning process in Dentistry by using an application that manages dental caries determinants. Material and methods: An application was used by students from a Dentistry Undergraduate Program from a public university in southern Brazil. Data collection comprised a qualitative study with Dentistry undergraduates, through focus group technique. Data analysis was performed according to Bardin’s content analysis. Results and Discussion: Results are presented in categories: 1. Use of ICTs in Dentistry teaching; 2. Students’ perceptions on the application; 3. The application as a teaching-learning tool in Dentistry. Data analysis showed advantages of using ICTs in dental teaching as key tools and process facilitators. The application is a decision-taking and action-planning tool, guiding students’ clinical reasoning towards recognition of local reality. Conclusion: Relevance and potential use of ICTs in Dentistry teaching was detected, making them auxiliary tools in students’ education in the face of their need to adapt to the current context of technological advances and the rapid expansion of scientific knowledge.